Zircon reconnaissance dating of Proterozoic gneisses along the Kunene River of northwestern Namibia - Kröner, A.; Rojas-Agramonte, Y.; Wong, J.; Wilde, Simon (Elsevier, 2014)
The northern margin of the Epupa Metamorphic Complex (EMC) along the Kunene River in NW Namibia is one of the geologically least known terranes in Africa because of its remoteness and difficult accessibility. We report field relationships and reconnaissance zircon ages for granitoid gneisses from a 120. km foot-traverse along the Kunene River between the Ruacana Falls in the east and Marienfluss in the west. Most rocks are late Palaeoproterozoic in age and correlate well with similar rocks of the EMC farther south in Kaokoland (1757-1835. Ma, one sample 1861. Ma) and with granitoid rocks in the Kamanjab Inlier, some 400. km SE of the Kunene River (1801-1836. Ma). All these rocks constitute a large magmatic province on the southwestern margin of the Congo Craton, whose protoliths are possibly related to arc magmatism during the Africa-wide so-called Eburnian event (ca. 2000. ±. 200. Ma). However, there are also Mesoproterozoic granitoids, 1520-1530. Ma in age, whose tectonic significance remains uncertain but which seem to document a thermal event also seen in high-grade metamorphism and isotopic resetting in this part of SW Africa.